Juvenile hormone controls ovarian development in female Anopheles albimanus mosquitoes - Hernández-Martínez, Salvador; Cardoso-Jaime, Víctor; Nouzova, Marcela; Michalkova, Veronika; Ramirez, Cesar E; Fernandez-Lima, Francisco; Noriega, Fernando G (Scientific reports, 2019)
Anophelinae mosquitoes are vectors of human malaria, a disease that infects hundreds of millions of people and causes almost 600,000 fatalities annually. Despite their medical importance, laboratory studies on key aspects of Anophelinae reproductive biology have been limited, and in particular, relatively little is known about the role of juvenile hormone (JH) in the control of female reproduction. The study presented here attempts to fill a gap of knowledge in our understanding of the JH control of ovarian development in female Anophelinae mosquitoes, using Anopheles albimanus as a model. Our studies revealed that JH controls the tempo of maturation of primary follicles in An. albimanus in a similar manner to that previously described in Aedes aegypti. At adult eclosion JH hemolymph titer was low, increased in 1-day old sugar-fed insects, and decreased in blood fed individuals. JH titers decreased if An. albimanus females were starved, and were reduced if insects emerged with low teneral reserves, precluding previtellogenic ovarian development. However, absolute hemolymph titers were lower than Ae. aegypti. Decapitation experiments suggested that if teneral reserves are sufficient, factors from the head activate JH synthesis by the corpora allata (CA) during the first 9-12 h after adult emergence. In conclusion, our studies support the hypothesis that JH controls previtellogenic ovarian development in female An. albimanus mosquitoes, in a similar manner that have been described in Culicinae.
Keywords: ženské pohlaví; corpora allata; Female; hemolymfa; Animals; Hemolymph; Ovarian Follicle; ovariální folikul; rozmnožování; juvenilní hormony; Reproduction; zvířata; Juvenile Hormones; Anopheles; Corpora Allata